1996
DOI: 10.1074/jbc.271.47.29637
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid and Adenine Cross-pathway Regulation Act through the Same 5′-TGACTC-3′ Motif in the Yeast HIS7 Promoter

Abstract: The HIS7 gene of Saccharomyces cerevisiae encodes a bifunctional glutamine amidotransferase:cyclase catalyzing two reactions that lead to the formation of biosynthetic intermediates of the amino acid histidine and the purine adenine. The HIS7 gene is activated by GCN4p under environmental conditions of amino acid starvation through two synergistic upstream sites GCRE1 and GCRE2. The BAS1p-BAS2p complex activates the HIS7 gene in response to adenine limitation. For this activation the proximal GCN4p-binding sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 29 publications
4
42
0
Order By: Relevance
“…The HIS7 promoter contains an ABF1 binding site approximately midway between two GCN4 binding sites at Ϫ231/Ϫ225 and Ϫ144/Ϫ139 bp relative to the translational start codon, and the region surrounding the ABF1 binding site and including both GCN4 binding sites has recently been shown to be nucleosome free (47,53). In addition, Bas1p/Bas2p can activate HIS7 via the Ϫ144/Ϫ139 site (48). The ABF1 binding site was found to be essential for basal transcription of a HIS7-lacZ fusion gene in gcn4 Ϫ yeast (47).…”
Section: Resultsmentioning
confidence: 99%
“…The HIS7 promoter contains an ABF1 binding site approximately midway between two GCN4 binding sites at Ϫ231/Ϫ225 and Ϫ144/Ϫ139 bp relative to the translational start codon, and the region surrounding the ABF1 binding site and including both GCN4 binding sites has recently been shown to be nucleosome free (47,53). In addition, Bas1p/Bas2p can activate HIS7 via the Ϫ144/Ϫ139 site (48). The ABF1 binding site was found to be essential for basal transcription of a HIS7-lacZ fusion gene in gcn4 Ϫ yeast (47).…”
Section: Resultsmentioning
confidence: 99%
“…In fungi, regulation of His biosynthesis is tightly co-ordinated with that of purine biosynthesis, through the BAS1p-BAS2p transcriptional complex which mediates the de-repression of several His biosynthetic genes in response to adenine limitation (Springer et al, 1996). In addition, His biosynthesis is regulated via the general nitrogen control mechanism by the bZIP transcription factor GCN4p.…”
Section: Regulation Of Histidine Biosynthesismentioning
confidence: 99%
“…In general, both Bas1 and Pho2 are required for transcriptional activation although one-carbon-unit metabolism genes are much more dependent on Bas1 than on Bas2/Pho2 (Denis and DaignanFornier 1998;Subramanian et al 2005). All the genes activated by Bas1 and Bas2/Pho2 also respond to extracellular adenine, their expression being low when adenine is abundant in the growth medium (Tice-Baldwin et al 1989;Daignan-Fornier and Fink 1992;Springer et al 1996;Denis and DaignanFornier 1998). To get an insight into the molecular mechanisms linking adenine availability to transcriptional activation, Rolfes et al (1997) used chimeras between LexA and either Bas1 or Pho2.…”
Section: Regulation Of Pyrimidine Metabolismmentioning
confidence: 99%
“…On the basis of proteome, transcriptome, and geneby-gene analysis, it was found that Bas1 and Bas2 activate the expression of all 10 AMP-biosynthesis genes except ADE16 (Daignan-Fornier and Fink 1992; ) and bind to a specific promoter region of these genes (Daignan-Fornier and Fink 1992; Rolfes et al 1997;Pinson et al 1998). Furthermore, Bas1/Bas2 also mediate adeninerepressible transcriptional activation of genes of other pathways metabolically connected to the purine pathway, such as histidine (HIS1, HIS4, and HIS7), glutamine (GLN1), or one-carbon-unit (SHM2, MTD1) metabolism genes ( Figure 15) (Arndt et al 1987;Springer et al 1996;. Bas1 binding to the promoter region of most of these genes has been confirmed in vivo by ChIP-CHIP analysis (Mieczkowski et al 2006).…”
Section: Regulation Of Pyrimidine Metabolismmentioning
confidence: 99%